ASUHAN KEBIDANAN PADA IBU NIFAS: TERAPI PEMBERIAN KURMA MENINGKATKAN HEMOGLOBIN DALAM DARAH - Muthia Darlina; Fadhiyah Noor Anisa; Siti Noor hasanah3 (Health Sciences Journal, 2026)
The prevalence of anemia among postpartum mothers in Indonesia remains high, at around 25% of the total postpartum population, Mild postpartum anemia can hinder recovery and increase the risk of infection and other complications. Dates are a natural food source rich in iron, vitamin B6, and antioxidants, which support red blood cell formation and restore energy in postpartum mothers. Objective: Providing midwifery care for postpartum mothers with mild anemia through date fruit therapy and evaluate its effect on increasing hemoglobin levels in Puskesmas Pekauman. Methods: A case report of Mrs. R, a 24-year-old postpartum mother with mild anemia and a hemoglobin level of 10.0 g/dL on the third day after delivery. The intervention included the consumption of 7 dates per day for 7 consecutive days, accompanied by health education, 1x1 tablet of iron (Fe) daily, direct monitoring by the researcher, and encouragement for rest and regular breastfeeding. Results: Following the intervention, the mother's hemoglobin level increased from 10.0 g/dL on day one to 11.1 g/dL. She also reported decreased symptoms of dizziness and weakness, along with improved motivation to breastfeed her infant. Conclusion: Date fruit therapy combined with education, daily monitoring, and iron supplementation is effective in increasing hemoglobin levels in postpartum mothers with mild anemia and supports overall postpartum recovery.